2016
DOI: 10.1371/journal.pone.0157550
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Gene Expression Differentiates between Atrial Fibrillation and Sinus Rhythm after Cardioversion

Abstract: BackgroundTreatment to restore sinus rhythm among patients with atrial fibrillation (AF) has limited long-term success rates. Gene expression profiling may provide new insights into AF pathophysiology.ObjectiveTo identify biomarkers and improve our understanding of AF pathophysiology by comparing whole blood gene expression before and after electrical cardioversion (ECV).MethodsIn 46 patients with persistent AF that underwent ECV, whole blood samples were collected 1–2 hours before and 4 to 6 weeks after succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…However, Lin et al (31) studied the association of whole blood gene expression with AF in a large community-based cohort, and identified 7 genes markedly upregulated with prevalent AF. Raman et al (32) also elucidated peripheral blood gene expression in patients with persistent AF that underwent electrical cardioversion. In another study, peripheral monocyte toll-like receptor (TLR) expression levels have been investigated and elevated TLR-2 and TLR-4 expressions were detected in patients with AF (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, Lin et al (31) studied the association of whole blood gene expression with AF in a large community-based cohort, and identified 7 genes markedly upregulated with prevalent AF. Raman et al (32) also elucidated peripheral blood gene expression in patients with persistent AF that underwent electrical cardioversion. In another study, peripheral monocyte toll-like receptor (TLR) expression levels have been investigated and elevated TLR-2 and TLR-4 expressions were detected in patients with AF (33).…”
Section: Discussionmentioning
confidence: 99%
“…Raman et al . 55 also evaluated peripheral blood gene expression in patients with persistent AF that underwent electrical cardioversion. In a recent study, peripheral monocyte toll-like receptor (TLR) expression levels have been investigated and higher levels of TLR-2 and TLR-4 expressions were detected in patients with AF 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of heart failure, it has been demonstrated that NT-proBNP is released primarily by the atria because of the increased myocardial contraction, volume load and wall stress caused by AF 19 . In previous studies including an analysis from this dataset, restoration of sinus rhythm through cardioversion led to a decrease in natriuretic peptides concentrations [20][21][22] . Our data extend these previous reports by demonstrating within-person reductions in NT-proBNP during a short-term follow-up in patients who were in sinus rhythm, and persistently elevated levels in those who remained in AF.…”
Section: Discussionmentioning
confidence: 75%